Peran Moderasi Kepemilikan Institusional pada Pengaruh Financial Slack terhadap Corporate Social Responsibility - Robert Jao; Ana Mardiana; Anthony Holly; Cristiani Djurnaidi (AKUNTANSI 45, 2024)
The purpose of this study is to analyze the effect of financial slack on corporate social responsibility (CSR) and analyze the role of institusional ownership as a moderator on the effect of financial slack on corporate social responsibility. This study uses stakeholder theory and agency theory to explain the relationship between variables. Sample selection used purposive sampling method. The population used in this study is all non-financial companies listed on the Indonesia Stock Exchange for the 2020 to 2022 period. The number of that met the criteria are 89 companies. The analytical method used is moderated regression analysis. The results of this study show that financial slack has a positive and significant effect on corporate social responsibility. Institutional ownership strengthens the influence between financial slack on corporate social responsibility and acts as a quasi moderation.